The suitability of folktales as a culturally responsive learning media in ELT classroom - Prasetya, Muhammad Wahyu; Yuliati (ELT Forum: Journal of English Language Teaching, 2025)
Despite the abundance of studies and articles regarding the subject of culturally responsive teaching, there is a noticeable scarcity of research that discuss the subject of learning media in the implementation of CRT specifically in English Language Teaching (ELT) classrooms. By analyzing much further about the subject of learning media in the scope of CRT, the findings would resulted in an enriched and increased learning resources to be utilized by the educator. In this article, the author would attempt to do so by analyzing the suitability of folk tales as a culturally responsive learning media, specifically the Indonesian folktales. To assess the suitability of the folk tales, this qualitative study employed a qualitative content analysis based on the key principles of culturally responsive pedagogy and ELT materials evaluation. Some of the most well known Indonesian folktales were chosen as the subject analysis. The findings indicated that folktales would be a suitable learning media both in terms of cultural and pedagogical. All of the subject of the research exhibit inherent cultural value that can resonate with the learners and educational value that can be utilized in various occasion. These findings provide valuable pedagogical insight on how folktales can be implemented as effective learning media in culturally responsive classroom.